Comparison of activity of three preparations of L-asparaginase in acute lymphoblastic and myeloblastic leukemia: the study of cytotoxicity and induction of apoptosis in cell lines - Kołodziej, Beata; Kuryło-Rafińska, Beata; Styczyński, Jan; Kubicka, Małgorzata; Dębski, Robert (Contemporary Oncology/Współczesna Onkologia, 2005)
Background: L-asparaginase is a hydrolase, an enzyme catalyzing the decay of L-asparagine, an endogenous amino acid necessary for the survival of some types of neoplastic cells, such as lymphoblasts. The elimination of L-asparagine from the environment of cancer cells leads to the cell cycle arrest in G1 phase, inhibition of DNA and protein synthesis, induction of apoptosis and eventually, cell necrosis. Aim of the study: to analyze cytotoxicity of 3 preparations of L-asparaginase and their effect on induction of selected mechanisms of apoptosis and cell cycle in cell lines of human acute myeloblastic and lymphoblastic leukemias. Material and methods: Cytotoxicity was assessed using the MTT assay of cytotoxicity and viability end-point type. Mechanisms of apoptosis induction, as measured by annexin V binding, synthesis of nitric oxide, changes in expression of caspase-3 and changes in the cell cycle after in vitro treatment with L-asparaginase, were determined by flow cytometry. Results: Cells of acute promyelocytic leukemia HL-60 showed a profile of sensitivity and induction of apoptosis, comparable to respective sensitivity and response in acute lymphoblastic leukemic cell lines, regardless of preparations of L-asparaginase used. The intensity of nitric oxide synthesis correlated with the early phase of apoptosis expressed by annexin V binding. Erythroblastoid cell line K-562 with FAB morphology M6 presented high resistance to all tested L-asparaginases and showed no induction of apoptosis. Conclusions: This study shows that there are different patterns of response to L-asparaginase among acute myeloblastic leukemias with respect to cytotoxicity and induction of apoptosis. The sensitivity of promyelocytic cell line HL-60 to L-asparaginase is similar to the sensitivity of T-lineage acute lymphoblastic leukemia cell lines, whereas K-562 cell line is resistant to all tested preparations of L-asparaginase.